Legality and Legal Protection of Marriages for Believers in the Almighty God in Central Java - Anggitariani Rayi Larasati Siswanta (Faculty of Law, Universitas Pekalongan, 2024)
According to data from the population census in 2022, there are 117,412 Indonesians who followed Believers in the Almighty God. Subsequently, the government must pay attention in the legality of marriage between believers. This research aims to analyze the legality and legal protection of believers in Central Java. Normative juridical research methods use secondary and primary data as support. The study's findings demonstrate that the legality of marriages of believers is already acknowledged. Problems arose when the Supreme Court Circular Letter No.2 of 2023 was issued because the state forbids marriages between individuals of different religions and beliefs. However, there are still marriages with different beliefs because the marriage registry will only record the marriage formally through the National Identity Card of the prospective bride and groomwhich only list the adherents of the belief even though their beliefs differ. Another problem is when the belief organization has not been registered, the marriage cannot be registered, because to register the marriage is the Certificate from the Belief Leader and proof that the belief organization has been registered.